Use of Point-of-Care Gastric pH Testing to Assess the Efficacy of Acid Suppression Therapy in the Neonatal Intensive Care Unit - Ekhaguere, Osayame A.; Padula, Michael A.; Jensen, Erik A. (American Journal of Perinatology, 2020)
Objective The use of acid suppression therapies in newborns lacks efficacy and is associated with adverse effects. Point-of-care (POC) assessment of gastric aspirate pH may provide an objective, noninvasive measure of gastric acidity in tube fed infants. We conducted the present study to characterize the POC gastric pH levels in gastric tube fed infants before and after initiation of enteral omeprazole or ranitidine.Study Design Retrospective cohort study of infants with gastric aspirate pH levels determined by POC pH strips. Gastric pH levels recorded during 7 days before and 14 days after medication initiation were compared using Wilcoxon's sign-rank tests.Results Among 307 evaluated infants, 284 (92%) had a median gastric pH level ≥4 in 7 days prior to ranitidine or omeprazole. In 14 days after medication initiation, the median gastric pH of infants with pretreatment median gastric pH < 4 increased to 4.5 and 5 (p < 0.01) in the ranitidine and omeprazole groups, respectively. There was no change in infants with pretreatment median gastric pH ≥4.Conclusion Among infants receiving gastric tube feedings and enteral omeprazole or ranitidine, only those with a pretreatment gastric pH level <4 demonstrated a significant increase in gastric pH. Validation of our findings against esophageal pH multichannel intraluminal impedance testing is needed.
Keywords: gastroesophageal reflux; point-of-care gastric pH; infants; preterm infants